Enhancing sepsis management: the role of dynamic heparin-binding protein monitoring in elderly patients - Miao, Lei; Liu, Dandan; Liao, Jingxian; Shen, Xiaozhu; Xie, Chunhui; Hu, Guangyun (Frontiers in Medicine, 2025)
BackgroundSepsis is a life-threatening condition with particularly high mortality rates among the elderly. This study investigates the dynamic monitoring of heparin-binding protein (HBP) levels as prognostic biomarkers to improve risk stratification and management in elderly septic patients.MethodsWe conducted a retrospective cohort study involving patients aged 65 and older who were hospitalized for sepsis. Data were extracted from electronic medical records, including demographic, clinical, and laboratory information. We analyzed the relationship between dynamic HBP levels and 28-day mortality using linear mixed-effects models to assess the effects of time and prognostic groups.ResultsAmong 386 elderly septic patients, the 28-day mortality rate was 20.73%. HBP levels were significantly elevated at all time points in the mortality group compared to the survival group (p < 0.001). The linear mixed-effects model indicated that time, prognosis group, and their interaction significantly influenced HBP levels. In the survival group, HBP levels decreased significantly over time, whereas the mortality group exhibited a smaller reduction, with HBP levels remaining elevated overall. The prognostic predictive ability of HBP improved at various time points, with the combined model of HBP and C-reactive protein (CRP) showing time-varying area under the curve (AUC) values: 0.728 on day 10, 0.744 on day 15, and 0.803 on day 20. The time-dependent ROC curve demonstrated that the combined model consistently exhibited superior discriminative ability throughout the follow-up period. Additionally, the time-dependent Cox regression model indicated that dynamic HBP levels effectively predicted 28-day mortality risk across all subgroups (p < 0.001).ConclusionDynamic monitoring of HBP levels may aid in risk stratification and support clinical decision-making. Further prospective studies are required to evaluate its clinical utility and potential impact on patient management.